2020
DOI: 10.3389/fpsyg.2020.00017
|View full text |Cite
|
Sign up to set email alerts
|

Improved Leadership Skills and Aptitudes in an Excellence EMBA Program: Creating Synergies With Dialogic Leadership to Achieve Social Impact

Abstract: Psychological research on leadership has demonstrated that it achieves social impact, particularly in the improvement of working environments and organizational performance. The understanding of the organizational context of leader behavior and its different components is crucial to analyzing the impact of leadership in organizations. The purpose of this study is to identify and analyze the transformation and change of leadership skills and aptitudes before and after the implementation of an excellence EMBA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Social sciences have made, and are increasingly making, contributions promoting social impact (Aiello et al, 2020 ) in education (Rios-Gonzalez et al, 2019 ; Yeste et al, 2019 ; Duque et al, 2020 ; Ruiz-Eugenio et al, 2020b ), ethnic and cultural minorities (Gómez et al, 2019 ; Khalfaoui, 2019 ; Garcia Yeste et al, 2020 ; Serradell et al, 2020 ), gender, sexuality and masculinities (Foraster and Morlà, 2019 ; Serrano Amaya and Ríos González, 2019 ; Merodio et al, 2020 ; Salceda et al, 2020 ), communication and digital media (Madrid et al, 2020 ; Pulido et al, 2020a , b ; Rodríguez et al, 2020 ) or occupation and organizations (Campos et al, 2020 ; Mara et al, 2020 ; Redondo-Sama, 2020 ; Tellado et al, 2020 ), among others. However, when we look at the scientific and theoretical production throughout the history of social sciences, a great fragmentation can be observed, having little interdisciplinarity and little connection between what authors in the different disciplines are contributing.…”
Section: The Fragmentation Of the Social Sciencesmentioning
confidence: 99%
“…Social sciences have made, and are increasingly making, contributions promoting social impact (Aiello et al, 2020 ) in education (Rios-Gonzalez et al, 2019 ; Yeste et al, 2019 ; Duque et al, 2020 ; Ruiz-Eugenio et al, 2020b ), ethnic and cultural minorities (Gómez et al, 2019 ; Khalfaoui, 2019 ; Garcia Yeste et al, 2020 ; Serradell et al, 2020 ), gender, sexuality and masculinities (Foraster and Morlà, 2019 ; Serrano Amaya and Ríos González, 2019 ; Merodio et al, 2020 ; Salceda et al, 2020 ), communication and digital media (Madrid et al, 2020 ; Pulido et al, 2020a , b ; Rodríguez et al, 2020 ) or occupation and organizations (Campos et al, 2020 ; Mara et al, 2020 ; Redondo-Sama, 2020 ; Tellado et al, 2020 ), among others. However, when we look at the scientific and theoretical production throughout the history of social sciences, a great fragmentation can be observed, having little interdisciplinarity and little connection between what authors in the different disciplines are contributing.…”
Section: The Fragmentation Of the Social Sciencesmentioning
confidence: 99%
“…Secondly, both "not what is easy" and "new" relate to individuals' adaptive ability in leading the self, whilst engaging in naturally motivating tasks (Inam et al, 2021). Thirdly, "question everything" refers to an intolerance of accepting negative experiences as detrimental, whilst asking questions to the self in order to develop self-trust and commitment, and embracing new ideas and opportunities (Campos et al, 2020).…”
Section: The Power Of Self-leadershipmentioning
confidence: 99%
“…It is a logical goal to create a healthcare environment that supports compassion, safety, and quality nursing practise. In terms of social science, it is indicated that leadership has demonstrated it has a social impact, especially in improving working environments and organisational performance (Campos et al, 2020). Hence, a proper understanding of the behavioural components is critical to determining corporate results.…”
Section: Analysis By Research Areasmentioning
confidence: 99%